Pengaruh Harga, Kualitas Produk, dan Kualitas Pelayanan, terhadap Kepuasan Pelanggan Chatime - Dian Grace Sagala; Anggiat Parlindungan; Lily Maryam Nst; Nursiah Fitri; Indra Siregar (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The rapid growth occurring in the contemporary food and beverage industry during this era of globalization, driven by increasingly consumptive lifestyles, is the phenomenon examined in this study. One of the popular contemporary beverages today is Chatime. Chatime is widely known, especially among millennials such as college students. However, Chatime still receives negative responses from some of its customers. This may happen due to differences in individual preferences and varying customer expectations, meaning what is liked by most people does not always satisfy everyone, which is a problem addressed in this study. The factors suspected to influence customer satisfaction with Chatime are price, product quality, and service quality. The purpose of this study is to determine the impact of price, product quality, and service quality on Chatime customer satisfaction among Business Administration students at Politeknik Negeri Medan. This study uses quantitative methods, including validity tests, reliability tests, classical assumption tests, and hypothesis testing. The data analysis technique employed in this research is multiple linear regression analysis using SPSS version 26, with a sample of 94 respondents. Data collection techniques used in this study include questionnaires and literature studies. Based on the research results, price (X1), product quality (X2), and service quality (X3) simultaneously and partially have a positive and significant effect on customer satisfaction (Y). The results of the coefficient of determination (R2) test show that the variables of price, product quality, and service quality can explain 73.8% of the influence on customer satisfaction, while the remaining 26.2% is influenced by other variables not included in this study.